CHARGE syndrome presenting with persistent hypoglycemia: case report and overview of the main genetic syndromes associated with neonatal hypoglycemia - Alessandra Consales; Beatrice Letizia Crippa; Lorenzo Colombo; Roberta Villa; Francesca Menni; Claudia Giavoli; Fabio Mosca; Maria Francesca Bedeschi (BMC, 2022)
Abstract Background CHARGE syndrome (CS) is an autosomal dominant genetic condition whose recognition in the neonatal period is complicated by considerable phenotypic variability. Pediatric patients with genetic disorders have a known high incidence of hypoglycemia, due to many concurring factors. To date, neonatal hypoglycemia is a feature poorly explored in the literature associated with CS. This paper adds to the existing literature on hypoglycemia in CS and provides a brief review of the mechanisms through which CS, as well as the main genetic syndromes associated with neonatal hypoglycemia, may determine it. Case presentation The patient was a term newborn, first-born daughter to non-consanguineous parents. At birth, axial hypotonia with slight hypertonia of the limbs, and dysplastic auricles were noted. The incidental finding of asymptomatic hypoglycemia led to the initiation of glucose infusion on the II day of life, continued for a total of 8 days (maximum infusion rate: 8 mg/kg/min). In-depth endocrinological examinations showed poor cortisol response to the hypoglycemic stimulus, with normal GH values, thyroid function and ACTH. In view of the suspected hypoadrenalism, oral hydrocortisone therapy was initiated. Inappropriately low values of plasmatic and urinary ketones supported the hypothesis of concomitant transient hyperinsulinism, not requiring therapy. A brain MRI was performed, documenting thinning of the optic nerves, non-displayable olfactory bulbs and dysmorphic corpus callosum. An eye examination revealed bilateral chorioretinal coloboma. Temporal bone CT scan showed absence of the semicircular canals. The unexpected findings of coloboma and absence of semicircular canals led to the suspicion of CS, later confirmed by the molecular analysis of CHD7. Conclusions It seems important to consider CS in the differential diagnosis of persistent hypoglycemia in newborns with specific anomalies. At the same time, it is advisable to consider the risk of hypoglycemia in children with CS, as well as other genetic syndromes. Awareness of the many possible causes of hypoglycemia in newborns with genetic conditions may help steer the investigations, allowing for an appropriate and timely treatment.